Factores parentales presentes en un niño con conductas agresivas de la ciudad de Bogotá D.C (2018)
The main objective of this research is to identify parental factors such as: parenting patterns, conformation of the family nucleus, affective expression, communication processes and personality traits of the mother, influence the aggressive behavior of a child under 10 years of age in the city of Bogotá DC For this, a study with a mixed approach, of a descriptive type, with a case study design is proposed. For the collection of information, two tests will be used, which are: CEPER III and (PSDQ) in order to identify parenting patterns and the personality style of the mother. As a complement, the application of a semi structured interview to the mother of the minor, the minor and an external person will be carried out in order to obtain more information about the factors previously studied and how these affect the aggressive behavior of the minor.